Head and neck imaging surveillance strategy for HPV-positive oropharyngeal carcinoma following definitive (chemo)radiotherapy. (April 2021) - Wong, Erin T.; Huang, Shao Hui; O'Sullivan, Brian; Persaud, Vincent; Su, Jie; Waldron, John; Goldstein, David P.; de Almeida, John; Ringash, Jolie; Kim, John; Hope, Andrew; Bratman, Scott; et al.
Highlights: Pattern of HN imaging surveillance varied significantly among clinicians. Residual lymph nodes without adverse features are common. Imaging surveillance reduces the need for neck dissection. Surveillance without further scan is safe after 2 scans with stable residual nodes. Routine imaging surveillance without symptom/sign does not have proven value. Abstract: Purpose: To describe the utilization pattern of head and neck (HN) surveillance imaging and explore the optimal strategy for radiologic "residual" lymph node (LN) surveillance following definitive (chemo)radiotherapy (RT/CRT) in human papillomavirus (HPV)+ oropharyngeal carcinoma (OPC). Methods: All HPV+ OPC patients who completed RT/CRT from 2012 to 2015 were included. Schedule and rationale for post-treatment HN-CT/MRI were recorded. Imaging findings and oncologic outcomes were evaluated. Results: A total of 1036 scans in 412 patients were reviewed: 414 scans for first post-treatment response assessment and 622 scans for the following reasons: follow-up of radiologic "residual" LN(s) (293 scans/175 patients); local symptoms (227/146); other (17/16); unknown (85/66). Rate of scans with "unstated" reason varied significantly among clinicians (3–28%, p  < 0.001) and none of them yielded any positive imaging findings. First post-treatment scans identified 192 (47%) patients with radiologic "residual" LNs. Neck dissection (ND) was performed in 28 patients: 16 immediately (6/16 positive), 10 after one follow-up scan (2/10 positive), and 2 after 2nd follow-up scan (1/2 positive). Thirty patients had >2 consecutive follow-up scans at 2–3-month intervals, and none showed subsequent imaging progression or regional failure. Conclusions: Pattern of HN imaging utilization for surveillance varied significantly among clinicians. Imaging surveillance reduces the need for ND. However, routine HN-CT/MR surveillance without clinical symptoms/signs does not demonstrate proven value in identifying locoregional failure or toxicity. Radiologic "residual" LNs without adverse features are common. If two subsequent follow-up scans demonstrate stable/regressing radiologic "residual" LNs, clinical surveillance without further imaging appears to be safe in this population.